Adjusting the length and direction of the redundant duodenal stent using a detachable snare and endoclips. Issue 5 (13th June 2018) - Sasaki, Takashi; Yoshio, Toshiyuki; Fujisaki, Junko
Abstract : Watch videos of this article.